Customer Equity Model: Analysis of Online Food Delivery Services in Indonesia - Nurul Fitriani Fadhilah; Neneng Nurlaela Arief (Profesional Muda Cendekia Publishing, 2023)
In the context of online food delivery services Gofood, Grab Food, and Shopee Food, this research intends to investigate the idea of customer equity model. Customer equity is a comprehensive indicator that measures the long-term worth of customers and is crucial in helping organizations make strategic decisions. This study intends to offer insights into customer acquisition, retention, and development of strategies for improving the overall performance and profitability of the online food delivery services by studying the customer equity model. The key concepts of value equity, brand equity and relationship equity, and digital journey are examined in this study. With surveys used to gauge consumer views and behaviors, the methodology of this study uses a quantitative research strategy to collect and evaluate data from customers who utilize online food delivery services and this study also analyze using the tool SMART PLS 4.